THE MODERN VARIANT SYSTEM OF THE TEACHING INSTEAD OF A TRADITIONAL METHOD (Journal of Pharmaceutical Negative Results, 2023)
The article talks about a practical usage of the multimedia encyclopedia  to one discipline, as well as to another group of disciplines. In this case, the educational module considered in the subject may be dedicated to a specific topic or concept. The improvement of encyclopedias relies on the development of modules, adding new ones, correcting or deleting outdated material, and development of the management system.